2021
DOI: 10.18805/ijar.b-4466
|View full text |Cite
|
Sign up to set email alerts
|

​Evaluation of Terminalia arjuna in Comparison to Taurine against Experimental Nephrotoxicity due to Cisplatin in Rats

Abstract: Background: Cisplatin is one of the most remarkable solutions in ‘the war on cancer’. Although cisplatin has been a mainstay for cancer therapy, its use is mainly limited by nephrotoxicity. The current study was aimed to evaluate the ameliorative potential of Terminalia arjuna (TA) in comparison to taurine against cisplatin toxicity. Methods: A total of 36 male Wistar rats were divided into 6 groups of 6 rats in each. Group 1 was normal control. Cisplatin @ 5 mg/kg b.wt was injected on day 1 to groups 2, 5 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This finding is consistent with a previous report (Helal and Said, 2020;Namratha et al, 2021) that showed marked liver injury in rats treated with MTX. Similarly other authors also deomonstrated that protective effect of resveratrol and vitamin-e in 5-flourouracil induced hepatotoxicity (Harish et al, 2021), Terminalia arjuna against Experimental Hepatotoxicity due to Cisplatin in Rats (Sneha et al, 2021) and postulated protective effects due to antioxidant properties of these plants. However, our study also found that the administration of B. monnieri, which has antioxidant properties, significantly reversed the changes in serum AST and ALT activities in the toxic control group.…”
Section: Histopathology Of Livermentioning
confidence: 81%
“…This finding is consistent with a previous report (Helal and Said, 2020;Namratha et al, 2021) that showed marked liver injury in rats treated with MTX. Similarly other authors also deomonstrated that protective effect of resveratrol and vitamin-e in 5-flourouracil induced hepatotoxicity (Harish et al, 2021), Terminalia arjuna against Experimental Hepatotoxicity due to Cisplatin in Rats (Sneha et al, 2021) and postulated protective effects due to antioxidant properties of these plants. However, our study also found that the administration of B. monnieri, which has antioxidant properties, significantly reversed the changes in serum AST and ALT activities in the toxic control group.…”
Section: Histopathology Of Livermentioning
confidence: 81%